Fast-acting insulin aspart in pediatric type 1 diabetes mellitus patients in a tertiary care center: Indian experience - Kochar, Inderpal Singh; Jain, Rakhi (International Journal of Advances in Medicine, 2023)
Background: The objective of this retrospective study was to evaluate the effectiveness and safety of fast-acting insulin aspart with additional drug excipients (L-arginine and niacinamide) in the Indian pediatric population. Methods: Data of pediatric type 1 diabetes mellitus (T1DM) outpatients in the age group of 1 to 18 years on treatment with injection degludec as long-acting Insulin OD and faster aspart as rapid-acting mealtime insulin 5-minutes before the meal for 20-weeks, was collected from the medical records of subjects. The primary endpoint was the mean change in glycated hemoglobin (HbA1c) and the secondary endpoints were mean changes in fasting plasma glucose (FPG) and 1 and 2-hour postprandial glucose (PPG), from baseline to 20-weeks post-treatment. The safety of treatment was also evaluated. Results: Data of 30 pediatric patients (Male: Female-14:16) with a mean age of 7.98 years was considered for this retrospective data analysis. Compared to baseline, there was a significant decline (p<0.001) in mean HbA1c levels by -0.72, in FPG by -32.87 mg/dl, in 1-hour PPG levels by -8.57 mg/dl, and 2-hour PPG levels by -11.3 mg/dl, after 20-weeks of treatment. Three and two patients reported symptomatic undocumented hypoglycemia and symptomatic documented hypoglycemia respectively, and one patient each reported local site reaction, and lipodystrophy. No episodes of nocturnal hypoglycemia were reported. Conclusions: In Indian pediatric T1DM patients 20-weeks mealtime faster aspart along with insulin degludec provided effective glycemic control, and treatment resulted in lower HbA1c, FPG, and 1 and 2-hour PPG levels. Conclusions: In Indian pediatric T1DM patients 20-weeks mealtime faster aspart along with insulin degludec provided effective glycemic control, and treatment resulted in lower HbA1c, FPG, and 1 and 2-hour PPG levels.